Market Orientation, Innovation, and Business Performance: The Mediating Role of Product Innovation in MSMEs of Nganjuk Regency - Eko Wahyu Puji Utomo; Sasi Utami; Yogi Yunanto; Enni Sustiyatik (INCOME: Innovation of Economics and Management, 2026)
Purpose – This study aims to examine the influence of market orientation on business performance, specifically testing product innovation as a mediating variable among culinary Micro, Small, and Medium Enterprises (MSMEs) in Nganjuk Regency, East Java, Indonesia. Design/methodology/approach – A quantitative, cross-sectional survey approach was employed. Data were collected using structured questionnaires (measured on a 5-point Likert scale) from 96 culinary MSME owners selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. Findings/Results – The results demonstrate that market orientation has a positive and significant effect on product innovation (β = 0.740, p = 0.000) and business performance (β = 0.362, p = 0.022). Additionally, product innovation positively and significantly influences business performance (β = 0.515, p = 0.001) and fully mediates the relationship between market orientation and business performance (β = 0.381, p = 0.000). Strong market orientation encourages relevant product innovations, which subsequently enhance sales, profitability, and overall business growth. Originality/Value – This study contributes to the literature on entrepreneurship and marketing management by empirically confirming the mediating role of product innovation specifically within the context of culinary MSMEs. It provides practical insights for MSME owners to boost competitiveness through market-driven innovation, and highlights the need for local governments to support these efforts through targeted training and development programs.